Membranoproliferative glomerulonephritis with masked monotypic immunoglobulin deposits - Larsen, Christopher P (Kidney Int, 2015)
The diagnosis of membranoproliferative glomerulonephritis (MPGN) has recently undergone change from an electron microscopy-based classification scheme to one based largely on immunofluorescence findings. This change is due to the recognition that many of these cases are driven by abnormalities of the alternative complement cascade, resulting in the concept of C3 glomerulopathy. Here we reviewed our case files to identify those with an MPGN pattern that show false negative staining for monoclonal immunoglobulins by routine immunofluorescence. Monoclonal immunoglobulin deposits were unmasked by performing immunofluorescence on formalin-fixed paraffin embedded tissue after protease digestion. Clinico-pathological details of 16 such cases with a mean serum creatinine of 2.7 mg/dl and mean 24 h proteinuria of 7.1 g were then determined. Hypocomplementemia was present in two-thirds of patients. Fourteen patients had a paraprotein on serum immunofixation, all of which matched the biopsy immunofluorescence staining pattern. Bone marrow biopsy showed plasma cell dyscrasia or B-cell lymphoproliferative disorder in 13 patients. Ten of these patients had findings on biopsy most consistent with C3 glomerulonephritis prior to performing paraffin immunofluorescence. Thus a high index of suspicion is necessary to avoid misdiagnosis in these cases, as many would have been mistakenly diagnosed as C3 glomerulopathy or unclassified MPGN if paraffin immunofluorescence was not performed.